Analysis of Rebound Rate of Wet Shotcrete Based on Experiment and Discrete Element Method - Chang Su; Zhuang Wu; Xiaokui Zheng (Shock and Vibration)
Wet shotcrete support is the main support method for underground engineering construction at present. The rebound rate is one of the indicators to evaluate the support effect, and a lower rebound rate will improve the construction effect of wet shotcrete. The concrete aggregates available in different regions of China have different particle sizes. To achieve better supporting effect, the discrete element method is used to simulate the spraying process of wet shotcrete. By constructing the nozzle structure and simplifying the concrete structure, the paper establishes the discrete element model of wet shotcrete. Using the above model, the paper analyzes the effects of injection distance and shrinkage angle on the injection rebound rate of concrete with three aggregate sizes of 5∼11 mm, 11∼17 mm, and 17∼25 mm. The optimal construction parameters of concrete with different aggregate particle size ratios were obtained through simulation experiments. The simulation results are highly consistent with the field experimental structure. It is feasible to simulate wet shotcrete spraying process by the discrete element method.